2021
DOI: 10.1186/s12940-021-00725-y
|View full text |Cite
|
Sign up to set email alerts
|

Aspartame and cancer – new evidence for causation

Abstract: Background Aspartame is one of the world’s most widely used artificial sweeteners and is an ingredient in more than 5000 food products globally. A particularly important use is in low-calorie beverages consumed by children and pregnant women. The Ramazzini Institute (RI) reported in 2006 and 2007 that aspartame causes dose-related increases in malignant tumors in multiple organs in rats and mice. Increased cancer risk was seen even at low exposure levels approaching the Acceptab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
42
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 25 publications
(51 reference statements)
0
42
0
2
Order By: Relevance
“…APM, an important sweetener, is commonly used in pharmaceutical processing and food processing, and its safety is highly controversial. Some studies have reported that APM is carcinogenic, causes immune deficiency, and induces brain tumors and other safety hazards in use . Although some of the sweeteners on the market have been replaced with relatively safer sweeteners such as glucose syrup by APM, its use is still widespread, and its overuse may affect people’s life safety in particular.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…APM, an important sweetener, is commonly used in pharmaceutical processing and food processing, and its safety is highly controversial. Some studies have reported that APM is carcinogenic, causes immune deficiency, and induces brain tumors and other safety hazards in use . Although some of the sweeteners on the market have been replaced with relatively safer sweeteners such as glucose syrup by APM, its use is still widespread, and its overuse may affect people’s life safety in particular.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that APM is carcinogenic, causes immune deficiency, and induces brain tumors and other safety hazards in use. 38 Although some of the sweeteners on the market have been replaced with relatively safer sweeteners such as glucose syrup by APM, its use is still widespread, and its overuse may affect people's life safety in particular. Thus, the potential neurological effects or toxicity of APM has been a hot topic of research.…”
Section: Discussionmentioning
confidence: 99%
“…Ashley Roberts, a consultant to the Calorie Control Council, a food-industry trade group that promotes the use of aspartame and other artificial sweeteners, ( https://caloriecontrol.org/about-the-council/ ” ) makes several incorrect and unsubstantiated claims in his response to our recent commentary, “Aspartame and Cancer – New Evidence for Causation” [ 1 ].…”
mentioning
confidence: 99%
“…A recent re-evaluation of the information regarding aspartame and cancer from studies conducted at the Ramazzini institute (RI) was published within Environmental Health [ 1 ]. This publication referenced additional analysis conducted by RI regarding aspartame induced haematopoietic and lymphoid tumours (HLT’s) in rats after life-time treatment [ 2 ].…”
mentioning
confidence: 99%
“…In conclusion, a close examination of the articles published by RI [ 1 , 2 ] who re-evaluated the HLT’s from the original life-time aspartame rat studies [ 8 10 ], and using INHAND criteria, provided insufficient evidence to challenge and contradict the opinions of both EFSA and the FDA regarding the “shortcomings and uncontrolled variables”, within the study “such as the presence of infection in the test animal”. For lymphocytic lymphoma, the histological images proved to be inconclusive since the relationship with surrounding tissues was not provided and the absence of inflammation in other organs was not reported.…”
mentioning
confidence: 99%